Dependence of the Properties of Dihydroindenofluorene Derivatives on Positional Isomerism: Influence of the Ring Bridging1. Issue 52 (7th November 2013) - Romain, Maxime; Tondelier, Denis; Vanel, Jean‐Charles; Geffroy, Bernard; Jeannin, Olivier; Rault‐Berthelot, Joëlle; Métivier, Rémi; Poriel, Cyril
<x xml:space="preserve">Abstract</x> Taking pole position: The relative position of the ring bridging has a unique and remarkable effect on the spectroscopic properties of dihydroindeno[1, 2‐a]/ [2, 1‐b]fluorenes (see picture). These blue‐emitting positional isomers have been successfully used as the emitting layer in organic light‐emitting diodes (OLEDs), with performance among the highest reported for dihydroindenofluorene‐based OLEDs.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>